Allergic Disease New Developments in Diagnosis and Therapy - Özdemir, Öner (IntechOpen, 2023)
This book provides a comprehensive overview of allergies, ranging from environmental allergies to food allergies. It discusses the diagnosis and management of allergic reactions, including early exposure to allergens, immunotherapy, and stem cell treatment. It includes eight chapters organized into four sections. Chapters discuss some of the most frequent allergic diseases, such as atopic dermatitis and chronic urticaria. There is also a chapter dedicated to treating allergies during the COVID-19 pandemic.